2021
DOI: 10.3389/fmars.2021.661158
|View full text |Cite
|
Sign up to set email alerts
|

Planktic Foraminiferal and Pteropod Contributions to Carbon Dynamics in the Arctic Ocean (North Svalbard Margin)

Abstract: Planktic foraminifera and shelled pteropods are some of the major producers of calcium carbonate (CaCO3) in the ocean. Their calcitic (foraminifera) and aragonitic (pteropods) shells are particularly sensitive to changes in the carbonate chemistry and play an important role for the inorganic and organic carbon pump of the ocean. Here, we have studied the abundance distribution of planktic foraminifera and pteropods (individuals m–3) and their contribution to the inorganic and organic carbon standing stocks (μg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 84 publications
(152 reference statements)
0
16
0
Order By: Relevance
“…For this comparison, we subdivided the regions by longitude to account for the different influences of Atlantic and Arctic waters, which play an important role for the abundances and habitats of planktonic foraminifera in this region (Pados and Spielhagen, 2014). The contribution of 10 % of planktonic foraminifera CaCO 3 fluxes to total CaCO 3 fluxes in the Fram Strait is in line with the lower end of the estimated contribution of planktonic foraminifera to total CaCO 3 fluxes at the northern Svalbard margin (4 %-34 %; Anglada-Ortiz et al, 2021). The higher contribution of planktonic foraminifera CaCO 3 fluxes to total CaCO 3 fluxes in the Greenland Sea is in the range of the estimates from Salter et al (2014) from the Crozet Plateau in the southern Indian Ocean, indicating that it falls within globally realistic ranges.…”
Section: Caco 3 Shell Mass Fluxmentioning
confidence: 60%
See 3 more Smart Citations
“…For this comparison, we subdivided the regions by longitude to account for the different influences of Atlantic and Arctic waters, which play an important role for the abundances and habitats of planktonic foraminifera in this region (Pados and Spielhagen, 2014). The contribution of 10 % of planktonic foraminifera CaCO 3 fluxes to total CaCO 3 fluxes in the Fram Strait is in line with the lower end of the estimated contribution of planktonic foraminifera to total CaCO 3 fluxes at the northern Svalbard margin (4 %-34 %; Anglada-Ortiz et al, 2021). The higher contribution of planktonic foraminifera CaCO 3 fluxes to total CaCO 3 fluxes in the Greenland Sea is in the range of the estimates from Salter et al (2014) from the Crozet Plateau in the southern Indian Ocean, indicating that it falls within globally realistic ranges.…”
Section: Caco 3 Shell Mass Fluxmentioning
confidence: 60%
“…Taking all possible biases in our flux estimation, as well as effects on the flux from Schiebel (2002), into account, our estimates cannot be considered as substantially deviating from his flux estimates for the North Atlantic. An opportunity to further validate our calcite flux estimates is given by a recent study from the northern Svalbard margin by Anglada-Ortiz et al (2021), who reported total foraminifera calcite fluxes of 2.3 to 7.9 mg CaCO 3 m −2 d −1 based on data from living planktonic foraminifera in the upper 100 m of the water column. It has to be considered that this might not represent the export flux zone, as at least two of the studied profiles show increasing shell abundance below 100 m. Nevertheless, considering that the planktonic foraminifera assemblages reported by those authors contained only about 50 % N. pachyderma, their minimum reported flux is similar to the range of the estimates in our dataset for the Barents Sea at 100 m (0.39 to 1.86 mg CaCO 3 m −2 d −1 using different weight averages for the calculation).…”
Section: Caco 3 Shell Mass Fluxmentioning
confidence: 93%
See 2 more Smart Citations
“…Indeed, in the adjacent Barents Sea, in the absence of sea-ice export, the Atlantification of the foraminiferal community appears stronger (Ofstad et al, 2020), likely further enhanced by import of nutrients that promotes phytoplankton production (Lewis et al, 2020). This means that once the ice export in the Fram Strait ceases to be fuelled by the increasing Arctic sea-ice reduction (Årthun et al, 2021;Guarino et al, 2020), the planktonic community will likely abruptly shift to a completely different state with more Atlantic and more non-sea-ice species, possibly impacting the carbon export of the region (Anglada-Ortiz et al, 2021). Observational data of sea-ice extent and future predictions plotted in Figure 1d show that, in the Fram Strait, the trend towards an increase in sea-ice export seems to have already reached its maximum.…”
Section: Discussionmentioning
confidence: 99%